2016
DOI: 10.1186/s13046-016-0303-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy to sensitive glioma to temozolomide treatment

Abstract: Temozolomide (TMZ), an alkylating agent, is widely used for treating primary and recurrent high-grade gliomas. However, the efficacy of TMZ is often limited by the development of resistance. Recently, studies have found that TMZ treatment could induce autophagy, which contributes to therapy resistance in glioma. To enhance the benefit of TMZ in the treatment of glioblastomas, effective combination strategies are needed to sensitize glioblastoma cells to TMZ. In this regard, as autophagy could promote cell surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
198
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(212 citation statements)
references
References 116 publications
14
198
0
Order By: Relevance
“…This finding is of clinical relevance and in addition with reports of SAS as a sensitizer for radiotherapy [31] could implement this xCT inhibitor as a new modality in glioblastoma therapy. But in comparison to TMZ, SAS–mediated effects on glioma cell survival did not appear to rely on significant alterations in the mechanism of autophagy [32]. Instead, SAS can induce ferroptosis in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of clinical relevance and in addition with reports of SAS as a sensitizer for radiotherapy [31] could implement this xCT inhibitor as a new modality in glioblastoma therapy. But in comparison to TMZ, SAS–mediated effects on glioma cell survival did not appear to rely on significant alterations in the mechanism of autophagy [32]. Instead, SAS can induce ferroptosis in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This kinase has a specific role in the DNA double-strand breaks repair, that is exercised in the nucleus, and a cytoplasmic function that is related to autophagy [33], a process that may be implied in therapy resistance [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an important mechanism for the regulation of sensitivity to radiation [9, 27]. We found that overexpression of miR-19b-3p or knockout of TNFAIP3 decreased apoptosis rates of NPC cell lines after irradiation.…”
Section: Discussionmentioning
confidence: 99%